Aktivitas Antifungi Ekstrak Etanol Daun Eryngium foetidum L. Terhadap Pertumbuhan Xeromyces sp. secara in vitro - Rikhsan Kurniatuhadi, Ines S Simatupang Elvi Rusmiyanto PW, (Universitas Tanjungpura, 2019)
Eryngium foetidum is a plant commonly used a seasoning cuisine and has a variety of chemical compounds that potentially an antifungal. The ethanol extract Eryngium foetidum was tested against fungal isolate Xi.01. The isolat Xi.01 isolated from the pepper (Piper Nigrum) stem was identified as Xeromyces sp. This study aimed to determine the ability of the antifungal ethanol extract of Eryngium foetidum against Xeromyces sp. (Xi.01). This study used solid dilution method and completely randomized design using 18 treatments, i.e negative control, positive control, diethanolamide concentration of 2.5; 5; 7.5 and 10% combined with the ethanol extract concentration of Eryngium foetidum of 5; 10; 20 and 40%. The results showed 16 treatment combinations had the same low antifungal activity level in the range 13,59-22,40%